Hyaluronic Acid‐Based Injectable Hydrogels for Wound Dressing and Localized Tumor Therapy: A Review. Issue 12 (26th October 2022) - Yang, Xu; Wang, Bin; Peng, Dongdong; Nie, Xiaobo; Wang, Jun; Yu, Cui-Yun; Wei, Hua
Abstract : Hyaluronic acid (HA)‐based hydrogels are regarded as ideal candidates for wound dressing and localized cancer treatment due to the excellent biocompatibility, potential targeting property, and highly adaptable structure for modulated functionalities. Among the numerous advantages, the injectable property is probably one of the most important factors that determines the therapeutic efficiency of HA‐based hydrogels as wound dressings because it enables to complete filling of wound sites, in situ encapsulation of any bioactive molecule, and sufficient adherence to wounds. Meanwhile, HA‐based injectable hydrogels can be used as localized drug delivery systems for cancer therapy with significantly compromised systematic side effects. Therefore, there is clearly considerable scope to compose a timely review on this hot subject of research. However, few reviews, as per knowledge, focus on this topic. For this purpose, the recent notable efforts made on the use of HA‐based injectable hydrogels as new‐type wound dressings and localized drug delivery systems with a focus on chemistry adopted to achieve desirable properties and functions for optimal performances are summarized. The useful information and guidelines summarized here are believed to promote next generation and clinical translations of HA‐based injectable hydrogels with greater therapeutic efficiency for wound dressing and localized tumor therapy. Abstract : The recent notable efforts made on the use of hyaluronic acid‐based injectable hydrogels as wound dressings and localized tumor therapy with a focus on chemistry adopted to achieve desirable properties and functions are summarized.